Directive illocutionary acts used in the English translation of the holy quran by Muhammad Asad: A corpus based study - Hapikry Surya Permana; Elvi Citraresmana (Proceedings of AICS - Social Sciences, 2017)
The aim of this research is to investigate the types of directive illocutionary acts and their functions appeared in the Holy Qur’an the translation edition. Austin (1962) was a pioneer in promoting the theory of Speech Acts then followed and developed by Searle (1976). Austin (1962) divided speech acts into locutionary, illocutionary, and perlocutionary acts. This research focuses on illocutionary acts. In addition, Searle (1976) in Cutting (2002) developed Austin’s theory and classified them into declaration, representative, commissive, directive and expressive. In order to find out the function of illocutionary acts appeared in The Holy Quran in translation edition, the writers apply the theory from Leech (1993). He divides the illocutionary function into four, there are competitive, convivial, collaborative and conflictive. Applying corpus linguistics as a tool of analysis is aimed to recover the frequentative verb of directive illocutionary acts in the holy Qur’an. Therefore, this research applies mixed method. By observing the frequentative verb of directive illocutionary acts used in the holy Qur’an, we will be able to analyze what kind of directive illocutionary acts are frequently used in the Holy Quran in translation edition? Who are the participants involved in the utterances? What are the messages conveyed in those utterances? According to the finding research there are three speakers and hearers. The first speaker is God to human as hearer. The second speaker is human to God as hearer. The last speaker is Satan to God as hearer. The results of the analysis show that there are two kinds of directive illocutionary act; they are commanding and requesting. While, the illocutionary function found is competitive. In addition, the most directive message used in the holy Qur’an is commanding with 575 words used.